Agile development methods for developing web application in small software firms - Ahmad, Faudziah; Baharom, Fauziah; Husni, Moath (2012)
Small software firms that involved with developing web application are lacked of well defined development process. Many development methods have been proposed for developing web application in these firms. However, these methods have some limitations.This paper aims to identify the agile development methods that are suitable for small development teams and determine the enhancements needed to get high quality web application.In order to achieve these objectives a comparative study was conducted on the suitable agile development methods that have been selected. Comparisons were made according to a set of criteria that include development process, project management, requirement, testing and design.The findings of this paper will be used as baseline for building a new measurable web application development methodology for small software firms.